Review: Classroom Interviews: A World of Learning - Catherine Compton-Lilly (Networks: An Online Journal for Teacher Research, 1999)
Garth Boomer once wrote, "To deliberately learn is to research." To Boomer, teachers and students are researchers when they purposely seek to understand aspects of their world. As a first grade teacher, it would be difficult for me to find a day of teaching that did not involve deliberate learning. Each day brings novel inquiries, new questions, and constant reflection on the events that transpire. Hopefully my students share this sense of wonder and interest as they learn to read, write, and research.